Molecular Docking on Kokosanolide A and C for Anticancer Activity Against Human Breast Cancer Cell MCF-7 - Sri Purwani; Julita Nahar; Zulfikar Zulfikar; Nurlelasari Nurlelasari; Tri Mayanti (Syarif Hidayatullah State Islamic University, 2021)
Kokosanolide A (1), from the seeds of Lansium domesticum Corr. cv Kokossan, has been shown strong cytotoxic activities (IC50 = 8.62 μg/mL) against MCF-7 breast cancer cells. The aim of this work was to study the molecular interactions of kokosanolide A and kokosanolide C with the Estrogen Receptor α (ERα) using computer-aided drug design approaches. Molecular docking using Autodock Vina (open-source software PyRx 0.8) was employed to explore the modes of binding of kokosanolide A (1) and kokosanolide C (2) with ERα. Compounds 1 and 2 showed strong bond-free energy (-8.8 kcal/mol and -8.7 kcal/mol) to ERα. These two compounds have a molecular mechanism to inhibit ERα in breast cancer cells.